THE EFFECT OF AUDIT ETHICS, AUDIT FEES, AUDITOR EXPERIENCE AND COMPETENCE ON AUDIT QUALITY IN THE PUBLIC ACCOUNTING FIRM (KAP) PADANG CITY - Zulvia, Dewi; Zusmawati; Fathiah (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2021)
This study aims to determine how much influence audit ethics (X1), audit fees (X2) Auditor Experience (X3) And Competence(X4), partially on the quality of the audit (Y) at the Padang city public accounting firm, using the data collection method in the form of a questionnaire as many as 66 respondents. In data analysis using validity and reliability tests. And the classical assumption test is normality test, multicollinearity, heteroscedasticity. The analysis method used is multiple regression linear regression analysis, coefficient of determinant, f test, t test, and r2 test using the SPSS16.0 tool. The results showed that the audit ethics variable had an influence on the audit quality variable, the audit fee in this study also had an influence on the audit quality variable, the Auditor's experience in this study had an influence on the audit quality variable and the competence in this study had an influence on on the audit quality variable